MATHEMATICAL COMMUNICATION ABILITY AND SELF CONFIDENCE Experiment with Eleventh Grade Students Using Scientific Approach - Sumarmo, Utari; Mulyani, Elis; Hidayat, Wahyu (IKIP SILIWANGI, 2018)
This study is a pre test-post test experiment with control group design having a goal to analyze the role of scientific approach on students’ mathematical communication ability (MCA) and self confidence (SC). The study involves 46 eleventh grade Vocational School students, a mathematical communication test, a mathematical self confidence scale (MSC), and a perception on scientific approach scale. The study found that on MCA and its Normalized Gain (N<G>), students getting treatment with scientific approach attained better grades than the grades of students taught by conventional teaching, but both student’s grades were still at low-medium level. On MSC, there was no different grades between students on both teaching approaches, and those grades were at medium level. The other findings, there is no association between MCA and MSC, and students performed high perception toward scientific approach.